Community Participation in Management of the Krueng Jreue Sub-Watershed, Krueng Aceh Watershed, Aceh Besar Regency - Sri Maulana; Hildanus; Kiki Rishki Ananda (Jurnal Ilmu Ilmu Kehutanan, 2024)
Government Regulation No. 37 of 2012 states that watershed management is a human effort to regulate the reciprocal relationship between natural resources and humans in the watershed and all its activities, in order to achieve sustainability and harmony of the ecosystem as well as increasing the benefits of natural resources for humans in a sustainable manner. Management of the Krueng Jreue Sub Watershed is important for efforts to maintain sustainability because the Krueng Jreue Sub Watershed is included in the upstream area which functions as a water absorption area which is important to maintain and manage, so that the utilization of the surrounding potential does not exceed its carrying capacity. The participation of communities living around the watershed area is important in efforts to preserve the function of the Krueng Jreue Sub-watershed. The aim of this research is to analyze community participation in the management of the Krueng Jreue Sub-watershed, Krueng Aceh Watershed, Aceh Besar Regency. This research was conducted in Gampong Sihom Lhok, Sihom Cot, Krueng Lamkareung, and Sinyeu, Indrapuri District, Aceh Besar Regency. This research method uses descriptive. The research results showed that community participation in planting trees in the management of the Krueng Jreue Sub-watershed was highest in Gampong Sihom Lhok, namely 28.7%, then community participation in the form of guarding the riverbank was highest in Gampong Sinyeu, namely 35.5%, and community participation in not throwing away the highest level of waste into the river is in Gampong Krueng Lam Kareung, namely 39.4%.